Peran Dukungan Sosial dan Penyesuaian Spiritual Ibu terhadap Tingkat Kecemasan Ibu Hamil Risiko Tinggi - Elly Susilawati; Yanti Yanti; Nora Veri; Ririn Widyastuti (Faletehan Health Journal, 2026)
Pregnancy can be a source of happiness and has the potential to cause anxiety for women. In Indonesia it is estimated that there were around 373,000 pregnant women experiencing anxiety. This study was to evaluate the effectiveness of family support and spiritual adaptation of high-risk pregnant mothers in reducing the level of anxiety. This study was conducted from March to October 2025 at a Health Center and a midwifery clinic in Pekanbaru, Indonesia, applying quantitative design with a descriptive analytical approach. The sample consisted of 120 high-risk pregnant women in the first, second, and third trimesters who made antenatal visits. Data were collected through interviews using questionnaires and analyzed by univariate analysis and Chi-Square test. The results showed that 48.3% of respondents were included in the category of high-risk pregnancies based on Poedji Rochjati's score. Most respondents had normal levels of anxiety (78.3%), good social support (79.2%), and high spiritual adaptation (75%). The majority of respondents received social support both (66.7%) and had high spiritual adaptation (70.8%) indicating normal levels of anxiety. In addition, most of the respondents in the low-risk category (32.5%) also had normal anxiety. The analysis showed a relationship between spiritual adaptation and the level of anxiety of pregnant women. Social support and spiritual adaptation play an important role in maintaining the psychological condition of high-risk pregnant women.